Direct synthesis of carbamate from CO2 using a task-specific ionic liquid catalyst. Issue 23 (6th November 2017) - Zhang, Qiao; Yuan, Hao-Yu; Fukaya, Norihisa; Yasuda, Hiroyuki; Choi, Jun-Chul
Abstract : An easily synthesized ionic liquid was used as an organocatalyst to synthesize carbamates directly from amine, CO2, and silicate esters. Abstract : A superbase-derived protic ionic liquid (IL, [DBUH][OAc]) catalyst was used to directly synthesize carbamate from an amine, CO2, and a silicate ester. This IL catalyst was easily prepared using its precursors, DBU, and acetic acid. Using 10 mol% of the catalyst under a CO2 pressure of 5 MPa in acetonitrile at 150 °C, carbamate was isolated in up to 96% yield. Specifically, aliphatic and aromatic amines were activated even though aromatic amines exhibited low activities because of their low p K a values. Other functional groups in amines were barely activated, affording exclusive chemoselectivity for amine activation. Isotope labeling experiments indicated that the proton in the counter cation is crucial in the catalytic cycle to produce water. In addition, a chemical shift corresponding to a mixture of aniline and [DBUH][OAc] was observed in the 1 H NMR spectrum, related to the formation of hydrogen bonds between aniline and basic acetate anions. The experimental results indicated that the designed IL catalysts require a protonated cation and a basic anion.